Penyuluhan Inovasi Pengolahan Puding Berbahan Daun Ginseng Jawa Untuk Kesehatan - Anita Swantari; Festivalia, Filma; Abduh, Muhammad Syaltut; Kusumaningrum , Anisa Putri (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This activity aims to introduce the potential of Javanese ginseng leaves in making pudding and provide in-depth education regarding the health benefits of this ingredient and how to process it. Counseling on the processing of Javanese ginseng leaf pudding was held at SMK Negeri 57, Jakarta, according to a schedule that did not interfere with academic activities. This activity aims to teach 53 students about the health benefits and techniques for making pudding from Javanese ginseng leaves. The program includes planning, socialization, and practice of making pudding. Afterwards, questionnaires will be collected to evaluate the impact of the program and adjust future materials. The Javanese ginseng leaf pudding education program at SMKN 57 Jakarta succeeded in increasing participants' knowledge and received positive feedback about the taste and health benefits. However, challenges such as low frequency of consumption and hesitation to buy again indicate the need for better marketing strategies and more in-depth education. It is recommended that the lecturer team improve marketing materials and packaging, as well as explore additional distribution channels. Students are expected to actively promote and educate about products to increase adoption and consumption.